Speech Acts and Leech’s Maxims in Presidential Insulting - Igaab, Zainab Kadim; Owaid, Intidhar Kadhim (Journal of Ecohumanism, 2024)
There are many verbal crimes that are punishable by law and they cause harm to the listener. An insult is one of these crimes and it can be defined as an unfriendly action in which speakers by saying or doing something rude or insensitive intends to affront their interlocutors. Linguistically, insults have traditionally been categorized as semantic items (words or phrases) conveying the communicative intention to hurt or injure psychologically an interlocutor. Although basically an insult is a verbal weapon used to offend, it very often becomes elaborate communicative acts that entail such complex levels of intentionality, cultural awareness or inferential processes that transcend this primary usage. Therefore, the “insulting” effects greatly depend on contextual attributes, and on the underlying intention together with the inferential conclusions on the part of the interlocutor. Accordingly, this study which is quantitative sets the following aims: Shedding light on the most common types of speech acts that are used to convey the insulting meaning and identifying the type of politeness maxim that is violated in the insulted messages. The researcher hypothesizes the following: assertive speech acts are the most frequent types of speech acts which are used to reflect insult and the most common violated politeness maxim in insult is tact maxim. The researcher adopts an eclectic model which consists of Speech Act Theory by Searle and Vanderveken (1985) and Leech’s Politeness Principle (1983-2014). This study arrives at the following: assertives are the most common speech acts but the indirect speech acts are more than the direct ones to express insult and the approbation maxim is the most violated maxim in the presidential speeches to express insult.